Wieseria bicepes sp. nov. (Nematoda: Oxystominidae) from the South China Sea - Jia, Susu; Huang, Yong (Zootaxa, 2020)
One unrecorded species of free-living marine nematodes from the South China Sea is described as Wieseria bicepes sp. nov. The present species is characterized by three circles of anterior sensilla nearly equal in length; four cephalic setae just behind the outer labial setae; oblong amphideal fovea with double contours and a handle-like protrusion at the base; tail tip bifurcate; spicules slightly curved with proximally cephalated and distally tapered; gubernaculum absent. The species is easily distinguished from the congeneric species by tail with a bifurcate tip and cephalic setae closely adjacent to labial setae.